Cost Efficiency Matters: Cost of Goods Sold as a Determinant of Manufacturing Company Profits - Dika Puspitaningrum; Naila Rafifah (Universitas Bumigora, 2026)
Manufacturing companies listed on the Indonesia Stock Exchange (IDX) operate in a highly competitive environment, where the Cost of Goods Sold (COGS) is the dominant cost component directly influencing profitability. Despite theoretical consensus that rising production costs reduce profit margins, empirical evidence remains inconclusive, creating a research gap, particularly within the Indonesian man- ufacturing sector. This study aims to empirically examine the effect of production costs on the profits of manufacturing companies listed on the IDX, with a cost-efficiency perspective. A quantitative approach with a causal research design was employed, using panel data from 204 manufacturing companies gener- ating 816 observations. The Fixed Effect Model (FEM) was selected as the best estimation model based on the Chow and Hausman tests. The empirical findings reveal that production costs have a significant and positive effect on corporate profits, suggesting that higher production costs do not necessarily reduce profitability but may reflect business expansion, increased production capacity, and improved product quality, which drive revenue growth. The novelty of this study lies in its application of Cost Efficiency Theory as the primary analytical lens, reframing production costs not merely as a financial burden but as a strategically managed resource. This perspective advances existing literature by demonstrating that the relationship between production costs and profitability is mediated by the effectiveness of cost management, offering a more nuanced understanding beyond the conventional cost-reduction paradigm.